PENGARUH DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PT BUMI SERPONG DAMAI Tbk PERIODE 2013-2022 - Nadilla, Ersya; Watiningsih, Ferdina (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether there is an effect of Debt to Equity Ratio on Return On Asset at PT Bumi Serpong Damai Tbk for the period 2013 - 2022, the effect of Total Asset Turnover on Return On Asset at PT Bumi Serpong Damai Tbk for the period 2013 - 2022, the effect of Debt to Equity Ratio and Total Asset Turnover on Return On Asset at PT Bumi Serpong Damai Tbk for the period 2013 - 2022. The type of research used is quantitative research using descriptive methods. The population in this study were all financial statements of PT Bumi Serpong Damai Tbk listed on the IDX. While the sample used is the balance sheet and income statement at PT Bumi Serpong Damai Tbk from 2013 - 2022. The data analysis method uses descriptive analysis descriptive analysis, classical assumption test, multiple linear regression test, coefficient of determination, partial t test and simultaneous F test. The results showed that: There is no partial influence of Debt to Equity Ratio on Return On Asset at PT Bumi Serpong Damai Tbk for the period 2013 - 2022. Evidenced by the tcount value -2.020 < t table 2.365 with a significant level of 0.083> 0.05. There is a partial effect of Total Asset Turnover on Return On Asset at PT Bumi Serpong Damai Tbk for the Period 2013 - 2022. Proven by the t-count value of 4.598> t table 2.365 with a significant level of 0.002 <0.05. There is a simultaneous influence of Debt to Equity Ratio and Total Asset Turnover on Return On Asset at PT Bumi Serpong Damai Tbk for the Period 2013 - 2022. Proven by the value of Fcount 24,769> Ftable 4,737 with a significant level of 0.001 <0.05. While the coefficient of determination is 84.1%, the remaining 15.9% is the influence of other variables.